AGRONOMIC BIOFORTIFICATION OF CROPS WITH SELENIUM IN BRAZIL AS A STRATEGY TO IMPROVE FOOD QUALITY - dos Reis, A.R.; Furlani Junior, E.; Moraes, M.F.; de Melo, S.P. (Revista Brasileira de Engenharia de Biossistemas, 2014)
There are conclusive evidences of Se deficiencies in Brazilian soils, pasture grass and agriculture products. Se deficiency values in soils are considered to range from 100 to 600 µg kg-1. However, in this mini-review, the highest Se content shown in Brazilian agriculture soils was approximately 210 µg kg-1 (very low Se levels). Genotypic variation of crops to accumulate Se in edible parts is an important agronomic trait to select or screening genotypes with high capacity to uptake and efficiency use of fertilizers. The amount of Se content in plants is strongly related to available Se in soils. There are evidences of low Se intake in Brazilian population, but no accurate and conclusive study has been done. Biofortification of crops with Se is not included in the HarvestPlus Program of Brazil. Therefore, more research on soil-Se levels and Se levels in agricultural products covering all Brazilian States is needed. It is well known that the application of Se containing fertilizers is efficacious at correcting low Se levels in human and animal diets such as in Finland, New Zealand and Australia.